PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY PADA PEMAHAMAN KONSEP SISWA - Witri Melfawani (Jurnal Edukasi dan Penelitian Matematika, 2018)
Understanding of mathematical concepts is important for students because it is basic ability, but in fact students’ understanding of mathematical concepts in SMPN 4 Padang grade eight is still low, so it needs to be improved because teachers use teacher centered learning in class. One attempt to overcome this problem is applied a learning model that can facilitates students to understand concepts and build their own knowledge. Learning model that can be applied is Cooperative Learning type Two Stay Two Stray (TSTS). Type of this research is quasi experiment with Static Group Design. Purpose of this research is to describes the impact from this model for understanding of mathematical concepts. Based on the result of data analysis by using t test, P-value = 0,011< ???? = 0,05, it can be concluded that understanding of mathematical concepts of students who studiying by cooperative learning type TSTS is better than students who study by conventional learning.Keywords — cooperative learning, two stay two stray, understanding of mathematical concepts, conventional learning.